ANALISIS DAN PERANCANGAN SISTEM INFORMASI PADA PT. OMEGA PADMA INDONESIA - Meilita Chintya; Tony Tony; Desi Arisandi (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
PT. Omega Padma Indonesia (OPI) is a company that is enganged in furniture and interior design. Currently, data processing and transaction activity in PT. OPI still manually.PT. OPI has a problems including requires time and effort to data searching,storing, and calculation, there is no record of the products flow, they still need a head count of the products, director does not get accurate information about transaction processes. The purpose of the analysis and design information system is to help company to resolve the existing problems, help company in processing and storing data, improve business processes effectively and efficiently. System development method used is SDLC (System Development Life Cycle) and Microsoft Visio as editor of the system design. The final result is to develop the information system that can resolve the problems in the company, will reach the maximal effort of working in the company and will save a lot of time in terms of managing the data of company.Key wordsAnalysis and design information system, company, information system, PT. OPI, system